EFFECT OF MIXING COLIGEN AND HEMORRHAGIC SEPTICARMIA VACCINES ON THE IMMUNE RESPONSE IN ANIMALS - A. Khalifa, Khalifa; J. Fiall, Tarik; A. Al-Jubouri, Kifah (The Iraqi Journal of Veterinary Medicine, 1988)
This study was done to evaluste the possible effect of mixing coligen vaccine prepared from E£. coli with hemorrhagic septicaemia vaccine prepared from P. multocida on the development of immmity. Awwasi sheep were used as experimental animals. A slight increase in the mean antibody titers in the animal group vaccinated with the mixed vaccine compared to the groups received each vaccine separately was noticed. Challenge experiment showed that protection against heterologous organiams by using homologous vaccine was low (12.5%) in comparison with the group received homologous vaccine (protection 87.5%). No detectable reaction tms noticed with the antisera and heterologous antigens.